The Effectiveness of Applying the Ice Breaking Technique of Guessing Pictures Assisted by Poster Media on Learning Motivation in History Subjects: Efektivitas Penerapan Teknik Ice Breaking Tebak Gambar Berbantuan Media Poster Terhadap Motivasi Belajar Dalam Mata Pelajaran Sejarah - Tantri Puspita Sari; Zulfa; Liza Husnita (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This paper discusses the existing problem is that students still lack interest in learning in the learning process when educators use the lecture method. Lack of student interest greatly influences students' learning motivation so that this has an impact on student learning outcomes. On this basis, this research focuses on the effectiveness of implementing Ice Breaking Picture Guessing with the help of poster media on learning motivation in history subjects. The aim of this research is to describe the effectiveness of the application of the Ice Breaking Image Guessing Technique assisted by Poster Media on Learning Motivation in History Subjects. The type of research used in this research is quantitative percentage. The sampling technique in this research was the Purposive Sampling technique, namely sampling based on certain considerations, so that a sample of class X ATR students was obtained with a total of 23 students and an average UTS score of 34.70% in history subjects. Data collection techniques through observation,questionnaires, interviews and documentation. The data obtained was then analyzed descriptively as a percentage. The results of the research conducted showed that the effectiveness of the Ice Breaking technique of guessing pictures assisted by poster media on learning motivation in history subjects in Class X ATR SMK N 1 Kerinci was categorized as very effective with a score reaching 88,51%. It can be concluded that the application of the Ice Breaking image guessing technique assisted by poster media can be said to be very effective, according to the criteria table because it reaches a frequency of 81% -100%.